PEMANFAATAN LIMBAH SANDBLASTING INDUSTRI PERKAPALAN MENJADI PRODUK BATA BETON PEJAL MENDUKUNG MATERIAL HIJAU - Nur Fajar Aprilia Sari; Luqman Cahyono; Amanda Rosalina; Maret’atus Sholihah; Ria Rismawati; Ovi Prina Gastriani; Muhammad Akbar Febianto (Yayasan Nusantara Hasana Berdikari, 2025)
Indonesia, as a maritime country, has industrial activities that generate a large amount of waste. One of the largest waste-producing sectors is the shipping industry, particularly from ship maintenance and repair activities in shipyards. In this industry, there is a process called sandblasting, which is used to clean ship surfaces from rust, old paint, and other contaminants. The silica sand used in this sandblasting process is classified as hazardous and toxic waste (B3 waste). This waste poses a risk of environmental pollution if not properly managed.The research problem in this study is how to utilize sandblasting waste as an alternative material in the production of solid concrete bricks. The objective of the study is to process this waste into technically and environmentally feasible solid concrete bricks. The methods used include chemical characterization of raw materials using XRF, making test specimens in the form of 50 × 50 × 50 mm cubes, and conducting compressive strength and TCLP (Toxicity Characteristic Leaching Procedure) tests. The results show that the A2 variation produced a compressive strength of 142 kg/cm², exceeding the SNI 03-0349:1989 standard for quality I concrete bricks, and the TCLP test results indicated that the levels of Cu and Cr met the quality standards set by Government Regulation No. 22 of 2021. Therefore, solid concrete bricks made from hazardous and toxic waste are considered feasible as an environmentally friendly alternative construction material.